Peripheral Ossifying Fibroma - Meenakshi Bhasin; Vinny Bhasin; Abhilasha Bhasin (Case Reports in Dentistry)
Intraoral ossifying fibromas have been described in the literature since the late 1940s. Peripheral ossifying fibroma (POF) is usually a fibroma of the gingival which shows areas of calcification or ossification. It is a nonneoplastic enlargement of gingiva. Due to its clinical and histopathological similarities, some POFs are believed to develop initially as a pyogenic granuloma that undergoes fibrous maturation and subsequent calcification. It has been suggested that POF represents a separate clinical entity rather than a transitional form of pyogenic granuloma or irritation fibroma. This paper describes a case report of a 60-year-old female patient reported with growth on gingiva in the upper left front region of mouth three years ago.